Effect of Colpexin Sphere on pelvic floor muscle strength and quality of life in women with pelvic organ prolapse stage I/II: A randomized controlled trial - Jittima Manonai (2018)
Introduction and hypothesis: Colpexin Sphere was effective for advanced pelvic organ prolapse. The aim of this study was to assess the effect of Colpexin Sphere in women with pelvic organ prolapse (POP) stage I or II on pelvic floor muscle strength, quality of life, and POP stage. Methods: Women were randomly divided into Colpexin Sphere with pelvic floor muscle exercise group and exercise only group for a 16-week period. They had Colpexin pull test and digital test every 4 weeks. Quality of life and POP stage were re-evaluated at the end of treatment. Results: Ninety-one women were recruited and 85 completed. Colpexin Sphere plus pelvic floor exercise improved pelvic floor muscle strength. There was no significant difference between both groups. Vaginal symptom score decreased in both groups while the stages of prolapse did not change. Conclusions: Colpexin Sphere plus pelvic floor exercise and exercise alone improved pelvic floor muscle strength. © The International Urogynecological Association 2011.